Pelatihan Penguasaan Kosakata Bahasa Inggris Pada Anak Usia Dini Di PAUD Adian Jaya Karang Sari - Ika Purnama Sari; Mohammad Hanafi Holle; Anita Purba; Iin Parlina; Rizky Khairunnisa Sormin (MANGENTE: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2023)
Education for early childhood is one of the determinants in the management of education to get next level. This is the first step for the children to get an education before they continue to the Elementary school level. In this period, the children begin to receive education which was the beginning of the academic knowledge, such as reading, writing and arithmetic (CALISTUNG). English language is not mother tongue but English is the second language. English language is international language which used throughout the world. Through this community service activity, our team proposing chose one media of English vocabulary mastery namely by using flash card media. This media is very effective for the childhood because through by the picture they can easily to understand and memorize the vocabulary in English. Flash card is the media that very helpful in remembering and reviewing material such as foreign language, symbol, formulation and others. Through this activity, the students will be able to listen to what teacher say through the picture, write to what is the students hear and seen, and the students be able to memorize was has been written. Through this activity, it is hoped that students will be able to mention the things around them in English language.Keywords: Training, Vocabulary, Flash car